O direito do trabalho pós-positivista: por uma teoria geral justrabalhista no contexto do neoconstitucionalismo - Eduardo Marques Vieira Araujo (2012)
This dissertation examines the need to take a new look about the Labor Law, from the philosophical and legal references of post-positivism and neoconstitutionalism. These moves boosted, by the thesis of the supremacy of the Constitution and the principles normativity, a paradigmatic shift in the science of law, which until then was based in legal positivism and normativity absence of constitutional orders. With theadvent of Democratic State of Law, legal science has evolved to avoid that atrocities against human dignity reoccur. The bases of the General Theory of Law and Constitutional Theory started to be built on a large concept of democracy, linked to the enjoyment of citizenship, reachable only through the implementation of fundamental rights and guarantees. These powers constitute the human dignity and, considering their interdependence, must be accomplished fully. In Brazil, the FederalConstitution lists foundations, objectives and rights that converge to the protection of this principle. However, despite the undeniable normative character of these precepts, social injustice perpetuates. One of factors that contributes to the maintenance of this situation is the violation of social labor rights. In this context, this work proposes a new vision about the Labor Law, based on the neoconstitucionals and post-positivists premises. This area of law, that concerns to a central value in Brazilian constitutional order the labor must be investigated in the light ofconstitutional principles that governs the fundamental rights and guarantees, not only through uncritical exegesis of Consolidation of Labor Legislation rules. The major challenges of the Brazilian society are in the Constitution, including those related to the world of work. The constitucional reading of the Labor Law is a requirement of aDemocratic State of Law, not an option. This study aims to report a reductionist understanding of Labor Law and demonstrate that the effectiveness of its rules constitutes an obligation against which no social regression may be imposed.